Concrete Ceramic Waste Slab (CCWS) - Mohd Mustafa Al Bakri, Abdullah; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Che Mohd Ruzaidi, Ghazali, Prof. Madya; Shamsul Baharin, Jamaludin, Prof. Madya (Malaysian Invention & Design Society (MINDS), 2010)
Mohd Mustafa Al Bakri Abdullah and his team won bronze for Concrete Ceramic Waste Slab (CCWS) at 17th International Invention, Innovation & Technology Exhibition 2006 (ITEX 2006), 19th - 21st May 2006 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.